Calcareous nannofossil assemblages across the Pliensbachian/Toarcian boundary at the Peniche section (Ponta do Trovão, Lusitanian Basin) - Mailliot, S. (2007)
The Peniche section has revealed moderately-to-well preserved calcareous nannofossil assemblages across the Pliensbachian/Toarcian boundary. This good record has allowed the proposition of a refined biostratigraphic scheme. The stage boundary, as defined by ammonites, is comprised within the NJ5b C. impontus (NW Europe; BOWN & COOPER, 1998) or the NJT5b L. sigillatus (Mediterranean Tethys; MATTIOLI & ERBA, 1999) nannofossil subzones. Since in the Lusitanian Basin a mixing of N- and S-Tethyan taxa is observed, both biozonation schemes can be applied. Some nannofossil events (mainly first occurrences) are observed earlier in Portugal than in other Tethyan settings. It is still unclear if these events are real first occurrences. A diversification phase occurred across the Pliensbachian/Toarcian boundary. This phase is well recorded at Peniche, where a change is observed passing from the Pliensbachian, when assemblages are dominated by muroliths, to the Toarcian showing assemblages where placoliths are abundant. A quantification of nannofossils per gram of rock shows that absolute abundances are the highest across the Pliensbachian/Toarcian boundary. Indeed, Peniche exhibits nannofossil abundances very high with respect to correlative levels in other Tethyan settings. The pelagic carbonate fraction (produced by nannofossils) is important in the marly hemi-couplets of Peniche. In some levels, nannofossils account for more than 50% of the total carbonate fraction.